Cutting after grafting affects the growth and cadmium accumulation of tomato. Issue 15 (8th December 2022) - Liang, Le; Xie, Yongdong; Li, Xiaomei; Lin, Lijin; Sun, Guochao; Li, Huanxiu; Liang, Dong; Xia, Hui; Wang, Xun; Tu, Lihua; Liao, Ming'An; Tang, Yi
ABSTRACT: Cuttings are asexual reproduction, and different vegetative organs of the plant can be selected as cuttings to grow into a new plant. Growth and cadmium (Cd) accumulation of cuttings taken from tomato ( Solanum lycopersicum ) plants non-grafted or grafted onto five different rootstocks were studied in a pot experiment. 'Zhongyanhong 6ʹ and 'Hongyu F1ʹ were non-grafted (CK) and were grafted onto Solanum torvum, Totosga, 'Dalishengen', 'Banzhen 18ʹ and 'Guozhen 1ʹ, respectively, planted in pots without Cd-contaminated soil. Cuttings were taken after one month, then grown in Cd-contaminated soil (10 mg kg −1 ) for three months. In 'Zhongyanhong 6ʹ cuttings, compared with non-grafted, grafting onto five rootstocks increased plant dry weight, grafting onto 'Banzhen 18ʹ and S. torvum increased plant height, grafting onto 'Banzhen 18ʹ and 'Guozhen 1' increased fruit fresh weight, grafting onto 'Guozhen 1ʹ and 'Dalishengen' reduced Cd content in fruit. In 'Hongyu F1ʹ cuttings, compared with non-grafted, grafting onto five rootstocks increased plant dry weight, grafting onto Totosga increased plant height, grafting onto S. torvum and Totosga increased fruit fresh weight, grafting onto 'Banzhen 18ʹ, 'Dalishengen', S. torvum and Totosga decreased Cd content in fruit. Cutting after grafting affects growth and Cd accumulation of tomato, which can provide a theoretical basis for the safe production of nightshade vegetables.